Rio Grande offshore naval pole: political strategies and the formation of a naval production complex - Ricardo Borges da Cunha; Aldomar Arnoldo Rückert (Geosul, 2019)
The objective of the article is to identify the policies and strategies employed in the formation of the Rio Grande Offshore Naval Pole. Highlighting the actions of the State, the programs elaborated for the national naval industry and the role of Petrobras in the restructuring of the sector. The discovery of the pre-salt propelled the national project and allowed the decentralization of activities. In the towns of Rio Grande and São José do Norte, four shipyards, with orders from the state, were installed that impacted the economy in different regions of the state. Despite the delivery of part of the platforms, cases of corruption involving the state and changes in policies for the sector have led to the stagnation of the naval industry. The dependence of the state actions left the region without perspective, with the new routes of the orders of Petrobras. The access of the national naval industry to the international trade is a solution for the sector.